Navigating The Media Maze: perceived work-life balance among women journalists - Norsiah Abdul Hamid; Khairunnisa Kamal Azi; Siti Syamsul Nurin Mohmad Yazam; Sabrina Mohd Rashid; Mohd Sobhi Ishak (Penerbit Universiti Kebangsaan Malaysia, 2024)
Maintaining a balance between work and personal life is a dream for anyone with multiple roles to play in their daily routines. Women journalists are no exception, and their work requires them to possess a broad range of knowledge and skills to deliver accurate and timely information to the public. Despite having multiple responsibilities in their personal lives, women journalists have embraced this challenge. However, issues such as long working hours, inflexible work schedules, excessive workloads, the dual responsibility of childcare, workplace discrimination, lack of support from supervisors and family, and the spillover of work into family life can make it challenging to maintain a healthy work-life balance. This study aims to explore the perception of women journalists towards work-life balance. The Spillover and Role Theories offer insights into the challenges faced by women journalists in balancing their personal and professional lives. The study conducted in-depth interviews with 16 journalists, including single and married women, working in various environments at the media headquarters and state bureau. The perception towards work-life balance was categorised into three themes: work and family environment, mental well-being, and personality traits. This article highlights the difficulties that women journalists face in managing their diverse roles during the convergence period of the media industry and emphasises the need to address work-life balance concerns in the Malaysian media sector.